Analysis of the Implementation of Target Costing in an Effort to Increase Profits (Case Study on CV. Astop Convection in Saguling District) - Vinka Miftahul Janah; Muhammad Sugiharto (Sean Institute, 2024)
Convection or business finished product is Wrong One type business Which own prospect market Which gone stop, remember growth resident Which increase Keep going continuously from year to year. The concept of Target Costing is very appropriate, as competition increases and the level of supply far exceeds the level of demand, so market forces have an increasingly greater influence on price levels. For this reason, Target Costing is needed to achieve company goals in terms of cost reduction , which will ultimately have an impact on competitive price levels. The main problem in this convection business is how to apply the Target Costing method in an effort to reduce production costs so that CV profits can be increased. Astop, then reduces production costs, contribution margins and kaizen costing. This research is classified as qualitative descriptive research where the focus is describing, recording, analyzing and interpreting findings through observation, interviews and documentation studies. The type of data analysis used in this research is data collection then data reduction and then conclusions or verification are drawn. Based on the results of the research conducted, the author concludes that the effect of applying the Target Costing method on CV Astop shows a significant increase in profits and is effective to apply. By implementing the Target Costing method, the company can increase profits by 5% from the previous 24% to 29%.